ASSSOCIATION BETWEEN MEDICATION ADHERENCE AND PATIENTS FACTORS WITH TYPE 2 DIABETES MELLITUS IN MAJMAAH CITY, KINGDOM OF SAUDI ARABIA - Tahir Ansari; Abdul Rahman Alhamad; Ahmed Aloreyfij; Bader Alshmas; Waqas Sami (Pakistan Armed Forces Medical Journal, 2020)
Objective: To explore the medication adherence in type 2 diabetes mellitus in Majmaah, Kingdom of Saudi Arabia and to find possible role of socio-demographic factors in determining adherence to medication among patients with type 2 diabetes mellitus.